The analysis of Managerial factors of fund management and financial performance towards the growth of small businesses in the Rice Milling industry in the center of West Java. - Mulyadi, Dedi; Pertiwi HS, Santi; Indah Bayunitri, Bunga (International Journal of Psychosocial Rehabilitation, 2020)
This study examines the phenomenon identified the weaknesses of small industrial entrepreneurs in terms of entrepreneurial spirit, competence, leadership and partnership role in the management of funds impact on the financial performance and the implications for business growth. The purpose of this study is to examine and analyze: (1). Entrepreneurial spirit, competence, leadership and partnership role. (2). The fund management. (3). Financial Performance (4). Business growth. (5). The influence of the entrepreneurial spirit, competence, leadership and partnership roles either partially or simultaneously to the management of funds. (6). Fund management influence on financial performance, (7). The influence of the financial performance of the business growth. The method used is descriptive verification. The technique used is the cross-section, the research carried out for a period of time (October 2010 - March 2011) of the 156 respondents entrepreneur’s paddy rice mill in the center of the district of West Java Indramayu, Karawang and Subang district. The sampling technique used was cluster random sampling. Methods of data analysis used to test the hypothesis of the research is the analysis of the path (path Analysis). The results showed that: (1). Entrepreneurial spirit, competence, leadership and partnership role quite well, (2). The fund management is quite good, (3). Good financial performance, (4). Good business growth, (5). A significant difference between the entrepreneurial spirit, competence, leadership and partnership role for the management of funds (6). The effect of management of funds towards firm’s financial performance, (7). A significant difference between the financial performance of the business growth.